Waqf Paradigm Transformation Strategy: Reconstructing Religious Curriculum and Digitalizing Reporting to Enhance Cash Waqf Literacy in Indonesia - Widya Asrika (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
This policy paper analyzes the urgent need for a transformation in Indonesia's waqf governance, which is currently hampered by the dominance of traditional paradigms, where the knowledge gap between static social waqf and productive waqf concepts has led to low literacy and a crisis of public trust in cash waqf instruments. This issue is critical as it causes the vast potential of the community's endowment funds to remain underutilized for poverty alleviation, with the public remaining focused on physical asset waqf. Using a descriptive-qualitative analysis methodology through literature studies and an evaluation based on William N. Dunn’s criteria, this paper examines various regulatory alternatives to identify the most effective and feasible solutions. The results and discussion indicate that the root of the problem stems from a religious education curriculum that is not yet adaptive and a managerial reporting system that lacks transparency, necessitating a reconstruction of knowledge through tangible policy interventions. Therefore, this paper recommends the enactment of a Minister of Religious Affairs Regulation concerning the integration of a contemporary waqf curriculum and the digitalization of an integrated reporting system as an instrument of accountability. The implementation of this strategy is expected to shift the public's philanthropic orientation from a